Implementasi Kurikulum 2013 Dalam Kreativitas Guru Dan Motivasi Belajar Siswa Terhadap Prestasi Belajar Siswa Pada Mata Pelajaran Akuntansi Kelas X SMK Muhammadiyah 2 Klaten Utara - Dwi Prasiwi, Ida, Tri Nur Wahyudi, S.Pd, MM (2017)
This research purpose is to determine: 1) The influence of teacher's creativity to achievement, 2) influence student motivation toward achievement, 3) influence the creativity of teachers and students' motivation to achievement, 4) if there is influence between the creativity of teachers to achievement, then how creativity is applied in teaching by implementing the curriculum 2013 according to student's perspective, 5) if there is an influence between students' learning motivation on achievement, then the motivation to learn how is applied in teaching by implementing the curriculum 2013 according to teacher's perspective. The type of this research is using mixed method of concurrent embedded model(mixed unbalanced) with associative quantitative descriptive approach. The population in this study were students of class X SMK Muhammadiyah 2 Accounting North Klaten with the number of 93 students. Samples taken as many as 93 students with saturated sampling technique. The data taken was obtained through documentation, interviews and questionnaires, which have previously been tested and tested for validity and reliability. Quantitative data analysis techniques used are multiple linier regression analysis, t test, F test while qualitative used is descriptive qualitative analysis. Based on the analysis of data obtained by multiple linear regression equation as follows: Y = 66.411 + 0.713 X1 + 0,535X2. This equation shows that the creativity of teachers and students' motivation effect on achievement. Based on the analysis and discussion can be concluded that: (1) Creativity teacher effect on student achievement. This was proven by that t count > t table is 3.551> 1.987 with the significant value of 5%,(2) Students' motivation effect on learning achievement. This was proven by that t count > t table is 2,716> 1,987 with the significant value of 5%,(3) The creativity of teachers and students' motivation effect on learning achievement. This is based on that f count> f table is 6.558> 3.098 with the significant value of 5%,(4) From the interview result that creativity used by teacher have an effect on to learning achievement, (5) From the interview result that high student learning motivation influence to learning achievement.